Professional English in use : intermediate to advanced : ICT - Remacha Esteras, Santiago, ....-; Marco Fabré, Elena, ....- (Cambridge : University Press, 2007)
Professional English in Use ICT is suitable for intermediate to advanced level learners of English. The book covers a wide range of topics on Information Communications Technology including word processing, financial software and databases, multimedia applications, email, web design and Internet security. It presents and explains new words in context and shows learners how to use them. Primarily designed as a self-study reference and practice book, it can also be used to supplement classroom work. Easy to use and written in a clear style, this book will be invaluable for anyone needing to improve their ICT vocabulary for work, home or study.
Keywords: Engels -- Taalgebruik -- ICT